PERANCANGAN APLIKASI LIGHT DEPENDENT RESISTOR (LDR) PADA PEMBANGKIT LISTRIK TENAGA SURYA UNTUK MENINGKATKAN ENERGI LISTRIK YANG DIHASILKAN SECARA OTOMATIS - Simamora, Antonius; Siburian, Jhonson Monang; Mutiara, Piala; Sitohang, Rasmi; Sinaga, Joslen; Sinurat, Fadlah Kaumenni (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
The purpose of this study is to design an application that utilizes Light Dependent Resistor (LDR) to increase the efficiency of solar power generation systems. The scope of this study includes the use of Light Dependent Resistor (LDR) in optimizing solar power generation systems, energy efficiency analysis, and the effect of changes in light intensity on solar panel performance. The methodology used is the method of data collection (case study) and data analysis obtained from experiments and designing applications using LDR to control the movement mechanism of solar panels to obtain light energy in real-time. The results show that the integration of this sensor can increase energy production by up to 23% compared to conventional fixed systems. This system not only increases the effectiveness of solar power generation but also contributes to reducing maintenance costs and supports sustainable energy practices. The conclusion of the study shows that automatic angle adjustment on solar panels increases energy capacity by 13-19% compared to panels with fixed angles. The average power generated reaches 11.57 watts, higher than 10.07 watts from fixed panels. The use of LDR also increases the intensity of light received.